Practices and Challenges of Environmental Sustainability in Tourism: Insights from Malino, Indonesia - Jasman (Politeknik Pariwisata Makassar, 2024)
This study aims to evaluate the implementation of environmental aspects in sustainable tourism development in Malino, Tinggimonjong District, Gowa Regency, using a quantitative descriptive method. Data collection was conducted through surveys to gather information on the application of environmental criteria in the area. Data analysis was performed using spatial overlay techniques to assess the extent of criterion implementation and identify areas needing improvement. The findings indicate that Malino has implemented 20 out of 27 relevant environmental criteria. These include waste management, greenhouse gas emission control, and eco-friendly transportation. However, some areas still require improvement, particularly regarding infrastructure and supporting services. The study also highlights the challenge of balancing tourism development with environmental conservation. Effective environmental management is crucial for ensuring tourism sustainability. The main conclusion is the need for better spatial planning and improved management practices to protect natural areas from negative impacts and ensure the long-term sustainability of tourism development in Malino.